2021
DOI: 10.3390/ma14154214
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Novel Electrodeposited Bond Coats for Thermal Barrier Coating Systems

Abstract: The increased demand for high performance gas turbine engines has resulted in a continuous search for new base materials and coatings. With the significant developments in nickel-based superalloys, the quest for developments related to thermal barrier coating (TBC) systems is increasing rapidly and is considered a key area of research. Of key importance are the processing routes that can provide the required coating properties when applied on engine components with complex shapes, such as turbine vanes, blades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The characterization of one-dimensional (1D) nanowires -like strong light-emitting, light absorption, and optical conductivity -can improve the light-emitting diodes (LEDs) performance, optical detectors, sensors, solar cells, field-effect transistors, and nanogenerators. For instance, nanowires of ZnO act as carrier conduction channels in photoelectric devices and reduce the carrier loss of light produced [145][146][147]. The LEDs' performance and nanowire-based detectors of photoelectric could be improved compared to tools based on thin films of polycrystalline [148,149].…”
Section: Photoelectron Devicesmentioning
confidence: 99%
“…The characterization of one-dimensional (1D) nanowires -like strong light-emitting, light absorption, and optical conductivity -can improve the light-emitting diodes (LEDs) performance, optical detectors, sensors, solar cells, field-effect transistors, and nanogenerators. For instance, nanowires of ZnO act as carrier conduction channels in photoelectric devices and reduce the carrier loss of light produced [145][146][147]. The LEDs' performance and nanowire-based detectors of photoelectric could be improved compared to tools based on thin films of polycrystalline [148,149].…”
Section: Photoelectron Devicesmentioning
confidence: 99%
“…In recent years, researchers have proposed various techniques to modify the surface of gas turbine blades. Among these methods are aluminide coatings [5], thermal Coatings 2023, 13,1928 2 of 13 barriers [6], arc plasma spray [7], sol-gel [8], and laser cladding [9,10]. However, research results have shown that some of the above technologies have limitations, such as low deposition efficiency, poor substrate and coating bonding, and poor process stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel-base superalloys are popular as base materials for hot components in industrial gas turbines such as blades or vanes due to their superior mechanical performance and high-temperature oxidation resistance [8]. On the other hand, the combustion gases' existence generates a harsh environment, as well as hot oxidation, which is inevitable when alloys are utilized at high temperatures for long durations of time [9]. Two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the processing methods can offer the necessary coating characteristics for engine parts with complicated forms, like blades, turbine vanes, etc. [9].The study scope of electrodeposition has not been realized to a wide extent as an alternative to traditional strategies of generating bond coats as well as their effectiveness in increasing the life cycle. Due to their ability to create dense, adherent scales for Al 2 O 3 , Alumina coverings are commonly utilized as overlays and as a connection cover for TBCs on hot-gas turbine blades and other parts [16,17].…”
Section: Introductionmentioning
confidence: 99%